2018
DOI: 10.3171/2016.12.jns161233
|View full text |Cite
|
Sign up to set email alerts
|

“Y-stent retriever”: a new rescue technique for refractory large-vessel occlusions?

Abstract: Long-awaited positive trial data have shown the efficacy of endovascular treatment in patients with ischemic stroke who arrive at the hospital within the first 6 hours with large-vessel occlusion of the anterior circulation. With the introduction of stent retrievers (SRs) for mechanical thrombectomy, efficient and safe large-artery recanalization treatment can be achieved. However, sometimes there are patients who do not attain complete flow restoration following attempts with traditional maneuvers. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Besides medical rescue approaches, stent placement and Y-stent-retriever maneuvers may serve as mechanical rescue approaches if an intracranial access was successfully established. [37][38][39] A recent cohort study has suggested that the higher recanalization rates achievable with rescue permanent intracranial stent placement translated into clinical benefit without increasing the risk of symptomatic intracerebral hemorrhage. Although further studies in other populations are needed to confirm these findings, the results promote permanent stent placement as a feasible rescue technique in cases of stent-retriever failures.…”
Section: Delayed Recanalization and Rescue Optionsmentioning
confidence: 99%
“…Besides medical rescue approaches, stent placement and Y-stent-retriever maneuvers may serve as mechanical rescue approaches if an intracranial access was successfully established. [37][38][39] A recent cohort study has suggested that the higher recanalization rates achievable with rescue permanent intracranial stent placement translated into clinical benefit without increasing the risk of symptomatic intracerebral hemorrhage. Although further studies in other populations are needed to confirm these findings, the results promote permanent stent placement as a feasible rescue technique in cases of stent-retriever failures.…”
Section: Delayed Recanalization and Rescue Optionsmentioning
confidence: 99%
“…After literature review, 24 cases with different site occlusions were included for pooled analysis from five published articles (8,9,(11)(12)(13)(14), including 19 cases with MCA, 1 with basilar terminus, and 4 with carotid terminus. Clinical outcome was unavailable in three patients with MCA occlusion and one patient with basilar terminus (9,12,13).…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…The two stent retrievers coordinates together to grip the clot. The technique has been used in refractory cases for occlusion at middle cerebral artery (MCA), basilar artery, and internal carotid artery (ICA) (8)(9)(10)(11). However, feasibility of this technique remains unknown owing to limited cases.…”
Section: Introductionmentioning
confidence: 99%
“…A method to promote several passes under distal filter protection is not covered by health insurance in Japan. Regarding the efficacy of a procedure to retrieve a thrombus by deploying two stent retrievers, a method to deploy two stents in the superior and inferior trunks to M1 segment for a thrombus at the MCA bifurcation and simultaneously collect them, [10][11][12][13] and a method to shift two stents back and forth or deploy them in parallel for retrieval of a long, large thrombus involving the ICA to MCA 14) was previously reported. However, to the best of our knowledge, no study has reported retrieval of a giant thrombus involving the CCA to ICA origin, as observed in our patient.…”
Section: Discussionmentioning
confidence: 99%